Histopathological Findings Related to ORISE™ Injectable Submucosa Lifting Agent Used in the Endoscopic Mucosal Resection of Bowel Neoplasms: A Review of Three Cases - Patricia N. Ibarra-Arzamendia; Mark G. Hanly (Hindawi Limited, 2020)
The use of nonsaline injectable lifting agents is now routine in the performance of endoscopic mucosal resection of bowel neoplasms (EMR). These agents are used to elevate the mucosa from the muscularis propria and permit more a complete resection of the lesion while mitigating risk of possible thermal injury to the bowel wall and thus preventing perforation. After injection, these new agents, which are replacing normal saline, often remain present in the tissues for some time following the procedure and may be identified in the resection specimens where they may mimic a number of other conditions such as mucin pools, lymphangiomas, granulomatous inflammation, and amyloid deposition. We describe the histological findings associated with the use of nonsaline injectable mucosal lifting agents. Awareness of these agents and their associated artefact may reduce misdiagnosis or the use of unnecessary ancillary studies and highlights the importance of proving relevant clinical information on submission of specimens for pathological examination.